COVID-19: Implementing a New Healthy Lifestyle and Tackle Vaccination Hesitancy - Arto Yuwono Soeroto; Nabila Nauli Asriputri (Jurnal Profesi Medika, 2021)
Coronavirus disease 2019 (COVID-19), which caused by SARS-COV-2, has spread globally. Pre-existing comorbidities such as diabetes, hypertension, cardiovascular disease, obesity, and malignancy may increase susceptibility to infection and the worsening of COVID-19. An unhealthy lifestyle in people with pre-existing comorbidities can worsen the condition and increase the risk of mortality and morbidity. During the 5M policy implementation, people tend to adopt unhealthy lifestyles, which lead to weight gain, dysregulated immune systems, increased cardiometabolic risk, and death. Therefore, implement a new healthy lifestyle to achieve health, good mental status, and prevent the worsening of pre-existing comorbidities. Given the importance of comorbidities control, we advised people with pre-existing diseases to monitor their condition using easy devices. Simple home aerobic exercise with minimal equipment is recommended to achieve adequate physical exercise. Vaccination also plays an important role in preventing severe COVID-19 progression and reducing disease transmission. Despite the importance of vaccines, we are still facing vaccination hesitancy, in which many people are still in doubt about getting the vaccination. It is important to show the data that the benefits of the COVID-19 vaccine far outweigh the potential risks. Health workers play a vital role in community education and health promotion.